Diagnóstico neuroinmunológico de meningoencefalitis eosinofílica producida por Angiostrongylus cantonensis - Alejandro Ramos Robledo (Revista Cubana de Investigaciones Biomédicas, 2019)
The diagnosis of angiostrongylus cantonensis meningoencephalitis is established by the presence of the helminth larvae in the cerebrospinal fluid, but this evidence is very difficult to find since the larvae are labile in this medium and are not frequently found. Because in Cuba, the presence of the parasite dates back to 1981 and this parasite is the only one that can cause this disease in the country, a review is carried out with the aim of reviewing the literature published on the subject to collect all the evidence that help the auxiliary diagnosis of eosinophilic meningoencephalitis. It is proposed that the study of the intrathecal synthesis of IgE and C3c, together with the pattern of local synthesis of IgA + IgG mainly and IgG1 + IgG2, are the most indicated. There are other proteins that could help as the intrathecal synthesis of C4 and to a lesser extent MBL.